Spillovers from good-news and other bankruptcies: Real effects and price responses - Baranchuk, Nina; Rebello, Michael J. (Journal of Financial Economics, 2018)
We model debt restructurings that could endogenously end in bankruptcy, and study spillovers to competitors’ operating decisions, profits, restructuring outcomes and security prices. We show that while bankruptcy could cause the firm’s share price to drop, bankruptcy always signals good news about the firm. We identify the conditions under which a bankruptcy also signals good news about competitors. We demonstrate that when a firm’s bankruptcy costs are relatively small, bankruptcy raises its share price while lowering the prices of competitors’ shares and debt as well as boosting the probability that they will enter bankruptcy. When there is little information asymmetry about the firm’s prospects, or the information asymmetry is about industry prospects, bankruptcy raises competitors’ share and debt prices and lowers their probability of bankruptcy.